119 Clinician experiences of 1 year of telemedicine heart failure clinics: the video-HF study. (4th June 2021) - Singhal, Arvind; Riley, Jillian; Cowie, Martin
Abstract : Background: Prior to Covid-19, telemedicine clinics in heart failure (HF) were rare, but social distancing measures and increased demands on health services resulted in a shift to 'remote by default' clinic appointments in many organisations across Europe. We evaluated clinician experiences of telemedicine to determine its potential use post-Covid-19. Methods: From 16th March 2020 all HF appointments at a specialist centre were telemedicine by default, with in-person appointments only in exceptional circumstances. HF clinicians were invited to participate in semi-structured interviews about their experiences of telemedicine consultations. Interviews were conducted using Microsoft Teams, recorded and transcribed verbatim. Each interview lasted approximately 30 minutes. Narrative data were explored by thematic analysis: the iterative coding and comparison of transcripts to identify themes. Analysis was performed until themes saturated. Results: Between 16th March 2020 and 15th March 2021, there were 2725 HF clinic appointments, 98.9% of which were by telemedicine. 8 clinicians were interviewed: 4 HF consultants, 3 HF specialist nurses and one training-grade doctor. Four key themes emerged ( figure 1 ): Time management – telemedicine consultations were perceived to be more efficient, owing to more focused assessments, less time between appointments and ability to multitask, but more administrative and preparation time was required. Clinicians felt less guilty keeping consultations brief, as patients had not travelled for their appointment.Information gathering – without physical examination clinicians relied more on objective data such as test results. Video was perceived as superior to telephone for assessing patients. Examination of oedema was possible by video, but more difficult and perceived to be less reliable.Rapport and relationships – telemedicine changed the patient-clinician interaction. Clinicians experienced difficulty establishing rapport with new patients by telephone; video was better than telephone, but clinicians felt that new patients were generally best assessed in-person to establish a 'connection' and relationship of trust. Choice and flexibility – clinicians expressed a fear of 'top-down' diktats on future delivery of care. This was exemplified by the quote '…the health service has got a great tradition of making up its mind as to what the patient thinks'. Clinicians felt telemedicine consultations would continue to play a major role, as they were considered more convenient for patients, but patient choice was essential. Figure 2 shows a word cloud generated from interview transcripts. Conclusions: Telemedicine HF consultations were acceptable for clinicians, but changed workflows, consultation dynamics, and how clinicians developed rapport and trust. Understanding these changes is essential for future delivery of care. We will now seek to understand the views of patients and their families. Conflict of Interest: Dr Singhal's salary is funded by a fellowship from Abbott